1986
DOI: 10.1002/pen.760260608
|View full text |Cite
|
Sign up to set email alerts
|

A study on polymer blending microrheology

Abstract: In this paper it is shown that the formation and subsequent breakup of threadlike particles are important disperging mechanisms and largely govern the morphology resulting from a polymer blending process. Experiments on the breakup of Newtonian threads surrounded by a second Newtonian fluid have been carried out and good agreement with Tomotika's theory is achieved. Experiments on the breakup of viscoelastic fluid threads showed the influence of shear thinning and stretch thickening effects of the fluids used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
0
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(143 citation statements)
references
References 11 publications
6
135
0
2
Order By: Relevance
“…This is in agreement with the recent findings of Liu [3] on co-continuous PA/ABS blends filled with nanosilica. These experiments also confirms the work of Elmendorp [10] who has found that the appearance of yield stress prevents grow of capillary instabilities which can be directly related to the coarsening rate. The effects described above can be found qualitatively in the (PS/CB)/PMMA blends, too (Fig.…”
Section: -4supporting
confidence: 78%
“…This is in agreement with the recent findings of Liu [3] on co-continuous PA/ABS blends filled with nanosilica. These experiments also confirms the work of Elmendorp [10] who has found that the appearance of yield stress prevents grow of capillary instabilities which can be directly related to the coarsening rate. The effects described above can be found qualitatively in the (PS/CB)/PMMA blends, too (Fig.…”
Section: -4supporting
confidence: 78%
“…The factor ffiffi 2 3 q originates from equaling the amplitude to the mean thread radius, which would give a neck radius of 0. 50 This estimate for the critical capillary number is likely to underestimate the true value, since the breakup of the thread is unavoidable even if the neck radius is not completely zero yet, and the growth rate of the distortion actually increases as the neck gets thinner.…”
Section: -12mentioning
confidence: 97%
“…Calculations have been performed, using for the interfacial tension a value of (T= 5~ lop3 N/m [Wu (1979), Elmendorp (1986)]. This interfacial tension can be decreased via the addition of compatibilizers to the blend.…”
Section: Thread Break-upmentioning
confidence: 99%
“…The morphology continuously adapts to changes in shear and elongational stress, deformation rate, total strain, processing time, and temperature [see e.g., Utracki (1989), Han (1981), Paul and Newman (1978), Paul and Barlow (1980), Meijer et al. (1988), and especially the references in Elmendorp (1986) and Elemans ( 1989)]. In order to obtain the desired properties in the final product, it is important to control the morphology during the different processing steps involved.…”
Section: Introductionmentioning
confidence: 99%